PENGARUH EVALUASI PEMBELAJARAN DARING TERHADAP HASIL BELAJAR MATA PELAJARAN PAI DI SMAN 5 BOGOR - Maspupah Yazid, Siti Tami; Lisnawati, Santi (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to describe the influence of online learning evaluation on the learning outcomes of PAI subjects at SMAN 5 Bogor. The method used in this study is ex-postfacto method with quantitative approach. The sample in this study was 22% of the population of 316 (72 respondents) with simple random sampling techniques. Then data collection techniques using observations, questionnaires and documentation. Evaluation of online learning using questionnaires with validity test results from 16 questions there are 14 questions proven valid and the results of the coefficient reliability test of 0.725 declared reliable. While the student's learning results are taken from UAS scores. Prerequisite tests are conducted with normality tests and linearity tests. Data analysis using simple linear regression with a 5% significance level. The results showed that: the effect of PAI online learning evaluation on student learning outcomes was shown with a value of Fcount = 5,811 Ftabel = 3,978 when compared to both Fcalculations of 5,795 > Ftabel = 3,978. Judging from the results of R square = 0.077 which means that the evaluation of online learning affects 7.7% of PAI learning outcomes and the rest is influenced by other factors.